Frontline Science: PECAM‐1 (CD31) expression in naïve and memory, but not acutely activated, CD8+ T cells. Issue 5 (31st July 2018) - Newman, Debra K.; Fu, Guoping; McOlash, Laura; Schauder, David; Newman, Peter J.; Cui, Weiguo; Rao, Sridhar; Johnson, Bryon D.; Gershan, Jill A.; Riese, Matthew J.
Abstract: Inhibitory cell surface proteins on T cells are often dynamically regulated, which contributes to their physiologic function. PECAM‐1 (CD31) is an inhibitory receptor that facilitates TGF‐β‐mediated suppression of T cell activity. It is well established in CD4 + T cells that PECAM‐1 is expressed in naïve recent thymic emigrants, but is down‐regulated after acute T cell activation and absent from memory cells. The extent to which PECAM‐1 expression is similarly regulated in CD8 + T cells is much less well characterized. We evaluated T cells recovered from mice after infection with a model intracellular pathogen and determined that, in CD8 + T cells, PECAM‐1 expression was strongly down‐regulated during acute infection but re‐expressed to intermediate levels in memory cells. Down‐regulation of PECAM‐1 expression in CD8 + T cells was transcriptionally regulated and affected by the strength and nature of TCR signaling. PECAM‐1 was also detected on the surface of human activated/memory CD8 +, but not CD4 + T cells. These data demonstrate that PECAM‐1 expression is dynamically regulated, albeit differently, in both CD4 + and CD8 + T cells. Furthermore, unlike memory CD4 + T cells, memory CD8 + T cells retain PECAM‐1 expression and have the potential to be modulated by this inhibitory receptor. Abstract : CD31 is expressed on both naïve and memory subsets in CD8 + T cells.